(untitled) (Archives of Pediatrics of Uruguay, 2025)
Introduction: oncological diseases are rare in pediatric patients but they cause significant morbidity and mortality. They manifest with non-specific symptoms, which facilitates diagnostic delay. Objective: understand clinical and evolutionary characteristics of children /adolescents hospitalized for oncological pathologies in a private health provider between 2010 and 2020. Methodology: Retrospective descriptive cohort study, including children under 18 years of age hospitalized for oncological diseases between 01/01/2010 and 12/31/2020. Their medical records were reviewed. The following were described: epidemiological, clinical and evolutionary characteristics. Results: during the evaluated time, 61 patients were hospitalized: 39 with solid tumors, 22 hematological. The incidence was 14/100,000, with an average of 5 cases/year. The average age at diagnosis was 5.9 years, 59% were under 5 years old. The most common types of cancer were: leukemia and neuroblastoma. The most frequent manifestations in hematological tumors were: fever and nonspecific symptoms; in solid tumors those linked to location. In 35 children the diagnosis was made in less than 30 days. Forty-seven patients received chemotherapy, of which 34 presented febrile neutropenia. 33 patients were cured, 2 remain in remission, 10 relapsed, and 16 died. Conclusions: the incidence of oncological diseases in the period analyzed was similar to that reported in the whole country. The most common type was leukemia. It predominated in children under 5 years of age. More than half were cured, a quarter of the patients died, results similar to those in higher-income countries. These results allow us to improve the care provided to these patients and their families.